Efficacy of pirfenidone for idiopathic pulmonary fibrosis: An Italian real life study. Issue 7 (July 2015) - Harari, S.; Caminati, A.; Albera, C.; Vancheri, C.; Poletti, V.; Pesci, A.; Luppi, F.; Saltini, C.; Agostini, C.; Bargagli, E.; Sebastiani, A.; Sanduzzi, A.; et al.
Summary Background In this retrospective Italian study, which involved all major national interstitial lung diseases centers, we evaluated the effect of pirfenidone on disease progression in patients with IPF. Methods We retrospectively studied 128 patients diagnosed with mild, moderate or severe IPF, and the decline in lung function monitored during the one-year treatment with pirfenidone was compared with the decline measured during the one-year pre-treatment period. Results At baseline (first pirfenidone prescription), the mean percentage forced vital capacity (FVC) was 75% (35–143%) of predicted, and the mean percentage diffuse lung capacity (DLCO) was 47% (17–120%) of predicted. Forty-eight patients (37.5%) had mild disease (GAP index stage I), 64 patients (50%) had moderate IPF (stage II), and 8 patients (6.3%) had severe disease (stage III). In the whole population, pirfenidone attenuated the decline in FVC (p = 0.065), but did not influence the decline in DLCO (p = 0.355) in comparison to the pre-treatment period. Stratification of patients into mild and severe disease groups based on %FVC level at baseline (>75% and ≤75%) revealed that attenuation of decline in FVC (p = 0.002) was more pronounced in second group of patients. Stratification of patients according to GAP index at baseline (stage I vs. II/III) also revealed that attenuation of decline in lung function was more pronounced in patients with more severe disease. Conclusions In this national experience, pirfenidone reduced the rate of annual FVC decline (p = 0.065). Since pirfenidone provided significant treatment benefit for patients with moderate-severe disease, our results suggest that the drug may also be effective in patients with more advanced disease.